CD8α− DC is the major DC subset which mediates inhibition of allergic responses by Schistosoma infection. (December 2014) - Liu, J.‐Y.; Lu, P.; Hu, L.‐Z.; Shen, Y.‐J.; Zhu, Y.‐J.; Ren, J.‐L.; Ji, W.‐H.; Zhang, X.‐Z.; Wu, Z.‐Q.; Yang, X.‐Z.; Yang, J.; Li, L.‐Y.; et al.
Summary Our and others' previous studies have shown that Schistosoma japonicum (SJ) infection can inhibit allergic reactions. We recently reported that DCs played an important role in SJ infection‐mediated inhibition of allergy, which was associated with enhanced IL‐10 and T regulatory cell responses. Here, we further compared the role of CD8α+ DC and CD8α− DC subsets for the inhibitory effect. We sorted CD8α+ DC (SJCD8α+ DC) and CD8α− DC (SJCD8α− DC) from SJ‐infected mice and tested their ability to modulate allergic responses in vivo. The data showed that the adoptive transfer of SJCD8α− DC was much more efficient than SJCD8α+ DC for the suppression of allergic airway eosinophilia, mucus overproduction, antigen‐specific IgE responses, and Th2 cytokines (IL‐4 and IL‐5). More importantly, we found that the transfer of SJCD8α− DC, but not SJCD8α+ DC, significantly increased IL‐10 and TGF‐β production following OVA exposure. As control, the transfer of DC subsets from naïve mice had no significant effect on allergic inflammation. In addition, SJCD8α‐DC expressed significantly higher IL‐10 but lower IL‐12, CD80 and CD86 than SJCD8α+ DC, fitting a tolerogenic phenotype. The results suggest that CD8α− DC is the predominant DC subset which is involved in the parasitic infection‐mediated inhibition of allergic inflammation and possibly through enhancing immunomodulatory cytokine (IL‐10 and TGF‐β) production.